Social Support and Academic Stress in Student- Athletes: The Mediating Effect of Academic Self-Efficacy - Rizal Cahya Ningrat (Universitas Muhammadiyah Malang, 2026)
Academic stress is a feeling of anxiety and pressure experienced by students,both physically and psychologically, due to academic demands. In the contextof student-athletes, the simultaneous demands of academic and sportingcommitments can increase the risk of academic stress. Therefore,psychological factors are needed to explain how social support can helpreduce this stress, one of which is through academic self- efficacy . Thisstudy aims to examine the effect of social support on academic stress instudent-athletes, with academic self- efficacy as a mediating variable .Participants in this study were 346 student-athletes aged 18–25 who had beenand were active in sports competitions for at least 1 year. Data analysis usedMediated Regression Analysis of Hayes ' model 4 in SPSS . The results of thisstudy indicate that academic self- efficacy partially mediates the relationshipbetween social support and academic stress in student-athletes. This meansthat social support not only directly reduces stress but also indirectly throughincreasing academic self- efficacy . This study has novelty by highlighting thesymptoms of academic stress and analyzing the role of academic self-efficacy that bridges the influence of social support on academic stress in thestudent-athlete group.